Design Against Fracture and Failure - Huda, Zainul; Bulpett, Robert; Lee, Kang Yong (Trans Tech Publications, Limited, 2010)
Volume is indexed by Thomson Reuters BCI (WoS).The aim of this book is to develop, in the reader, the necessary skills required for designing materials, components and structures so as to resist fracture and failure in engineering applications.